Determining the originating conditions for the formationof the geochemical pattern of groundwater in Lattakia Governorate - كنان راعي (Latakia University Journal -Biological Sciences Series, 2022)
This research was conducted to a Hydrogeochemical study of specific ground water wells in Lattakia Governorate. This aims at specifying water quality and origion in order to plan the optimum future ways of using water supplies in the region. by collecting 20 water samples from wells distributed over most of the formations in the research area during the year 2015, and conducting some chemical analyzes for them, and then treating those results And use of "Sulin’s" Diagram to determine the origin of groundwater, It was found that these waters are of atmospheric (continental) origin, In addition to the presence of a number of minerals in it Calculated and emphasized the major role played by the percolation cycle in shaping the chemical composition of groundwater in the region, It also showed the geochemical ratios the groundwater in the area is fresh water rreflect the natural proportions of the hydrological cycle, And that the marine influence on the origin of the chemical composition of those waters is very small This can be manifested in some areas near the sea Especially during periods of over-pumping of groundwater, and The groundwater in the research area was classified bicarbonate-calcareous-magnesian type According to the "Piper" and "Stiff" Diagrams.